NRBF2 is a RAB7 effector required for autophagosome maturation and mediates the association of APP-CTFs with active form of RAB7 for degradation. Issue 5 (4th May 2021) - Cai, Cui-Zan; Yang, Chuanbin; Zhuang, Xu-Xu; Yuan, Ning-Ning; Wu, Ming-Yue; Tan, Jie-Qiong; Song, Ju-Xian; Cheung, King-Ho; Su, Huanxing; Wang, Yi-Tao; Tang, Bei-Sha; Behrends, Christian; et al.
ABSTRACT: NRBF2 is a component of the class III phosphatidylinositol 3-kinase (PtdIns3K) complex. Our previous study has revealed its role in regulating ATG14-associated PtdIns3K activity for autophagosome initiation. In this study, we revealed an unknown mechanism by which NRBF2 modulates autophagosome maturation and APP-C-terminal fragment (CTF) degradation. Our data showed that NRBF2 localized at autolysosomes, and loss of NRBF2 impaired autophagosome maturation. Mechanistically, NRBF2 colocalizes with RAB7 and is required for generation of GTP-bound RAB7 by interacting with RAB7 GEF CCZ1-MON1A and maintaining the GEF activity. Specifically, NRBF2 regulates CCZ1-MON1A interaction with PI3KC3/VPS34 and CCZ1-associated PI3KC3 kinase activity, which are required for CCZ1-MON1A GEF activity. Finally, we showed that NRBF2 is involved in APP-CTF degradation and amyloid beta peptide production by maintaining the interaction between APP and the CCZ1-MON1A-RAB7 module to facilitate the maturation of APP-containing vesicles. Overall, our study revealed a pivotal role of NRBF2 as a new RAB7 effector in modulating autophagosome maturation, providing insight into the molecular mechanism of NRBF2-PtdIns3K in regulating RAB7 activity for macroautophagy/autophagy maturation and Alzheimer disease-associated protein degradation.. Abbreviations: 3xTg AD, triple transgenic mouse for Alzheimer disease; Aβ, amyloid beta peptide; Aβ1-40, amyloid beta peptide 1–40; Aβ1-42, amyloid beta peptide 1–42; AD, Alzheimer disease; APP, amyloid beta precursor protein; APP-CTFs, APP C-terminal fragments; ATG, autophagy related; ATG5, autophagy related 5; ATG7, autophagy related 7; ATG14, autophagy related 14; CCD, coiled-coil domain; CCZ1, CCZ1 homolog, vacuolar protein trafficking and biogenesis associated; CHX, cycloheximide; CQ, chloroquine; DAPI, 4ʹ, 6-diamidino-2-phenylindole; dCCD, delete CCD; dMIT, delete MIT; FYCO1, FYVE and coiled-coil domain autophagy adaptor 1; FYVE, Fab1, YGL023, Vps27, and EEA1; GAP, GTPase-activating protein; GDP, guanine diphosphate; GEF, guanine nucleotide exchange factor; GTP, guanine triphosphate; GTPase, guanosine triphosphatase; HOPS, homotypic fusion and vacuole protein sorting; ILVs, endosomal intralumenal vesicles; KD, knockdown; KO, knockout; LAMP1, lysosomal associated membrane protein 1; MAP1LC3/LC3, microtubule associated protein 1 light chain 3; MLVs, multilamellar vesicles; MON1A, MON1 homolog A, secretory trafficking associated; NRBF2, nuclear receptor binding factor 2; PtdIns3K, class III phosphatidylinositol 3-kinase; PtdIns3P, phosphatidylinositol-3-phosphate; RILP, Rab interacting lysosomal protein; SNARE, soluble N -ethylmaleimide-sensitive factor attachment protein receptor; SQSTM1/p62, sequestosome 1; UVRAG, UV radiation resistance associated; VPS, vacuolar protein sorting; WT, wild type.